2016
DOI: 10.1021/acsenergylett.6b00402
|View full text |Cite
|
Sign up to set email alerts
|

CsSnBr3, A Lead-Free Halide Perovskite for Long-Term Solar Cell Application: Insights on SnF2 Addition

Abstract: Solar cells based on “halide perovskites” (HaPs) have demonstrated unprecedented high power conversion efficiencies in recent years. However, the well-known toxicity of lead (Pb), which is used in the most studied cells, may affect its widespread use. We explored an all-inorganic lead-free perovskite option, cesium tin bromide (CsSnBr3), for optoelectronic applications. CsSnBr3-based solar cells exhibited photoconversion efficiencies (PCEs) of 2.1%, with a short-circuit current (J SC) of ∼9 mA cm–2, an open ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
256
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(276 citation statements)
references
References 22 publications
10
256
0
10
Order By: Relevance
“…The last two years have witnessed a tremendous surge in reports based on replacing the Pb in PSCs with nontoxic/less toxic transition metals. Gupta et al employed CsSnBr 3 as a light absorber, which showed a PCE of 0.6%. Liu et al prepared a mixed‐cation‐based (CH 3 NH 3 ) 0.9 Cs 0.1 SnI 3 light absorber and developed a PSC device, but the efficiency was found to be very poor (0.3%).…”
Section: Methodsmentioning
confidence: 99%
“…The last two years have witnessed a tremendous surge in reports based on replacing the Pb in PSCs with nontoxic/less toxic transition metals. Gupta et al employed CsSnBr 3 as a light absorber, which showed a PCE of 0.6%. Liu et al prepared a mixed‐cation‐based (CH 3 NH 3 ) 0.9 Cs 0.1 SnI 3 light absorber and developed a PSC device, but the efficiency was found to be very poor (0.3%).…”
Section: Methodsmentioning
confidence: 99%
“…[141] Specially, with regard to Sn 2+ -containing perovskite NCs (e.g., CsSnX 3 ) and related devices, progress was strongly hampered by the transforming from Sn 2+ to Sn 4+ because Sn 2+ can easily be oxidized into Sn 4+ under ambient conditions. An in-situ protective strategy including introduction of reducing reagent such as tri-n-octylphosphine and hypophosphorous acid, [72,142] as well as additives like SnF 2 and SnBr 2 , [143][144][145][146] can improve the oxygen resistance and increase the stability under operating conditions. [64,110,142] In this case, the conventional coating technique to great extent cannot work efficiently.…”
Section: Stability Issuesmentioning
confidence: 99%
“…22,[51][52][53][54][55][56][57][58][59] Indeed, there are now numerous indications that the appealing optoelectronic properties of the hybrid perovskites are qualitatively matched by their all-inorganic analogues. 54,[60][61][62][63][64] In order then to delineate the properties and functionality of the molecular cations from those of the inorganic framework, one must first complete the description of the structure and dynamics of each. To this end, we employ solid-state NMR, a technique which is proved crucial for the study of plastic crystals.…”
mentioning
confidence: 99%